Trade Openness and Volatility - Levchenko, Andrei; Di Giovanni, Julian (Washington, D.C. : International Monetary Fund, 2008)
This paper examines the mechanisms through which output volatility is related to trade openness using an industry-level panel dataset of manufacturing production and trade. The main results are threefold. First, sectors more open to international trade are more volatile. Second, trade is accompanied by increased specialization. Third, sectors that are more open are less correlated with the rest of the economy. The point estimates indicate that each of the three effects has an appreciable impact on aggregate volatility. Added together they imply that the relationship between trade openness and overall volatility is positive and economically significant.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet